The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1159/000118032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin on Testicular Damage in Streptozotocin-Induced Diabetes Rats

Abstract: Background: It is well known that diabetes mellitus is associated with impairment of testicular function. In the present study, we aimed to demonstrate the effect of melatonin on testicular damage in male rats with streptozotocin (STZ)-induced diabetes. Methods: Male Wistar rats were divided into 4 groups: (1) control group, (2) melatonin-treated nondiabetic group, (3) diabetic group and (4) melatonin-treated diabetic group. Diabetes was induced by STZ injection. Melatonin was administered intraperitoneally at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
95
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(128 citation statements)
references
References 73 publications
23
95
0
4
Order By: Relevance
“…However, melatonin administration in late afternoon had decreased diameter of seminiferous tubule in non-PE hamster and mice (Ng & Ooi; Ooi & Ng). Nonetheless, if the antioxidant activity considered of the melatonin, we noted that melatonin administration increased the diameter of the seminiferous tubules in the diabetic rats (Guneli et al, 2008), healed the harmful effects of the radiation in the testis, restarted the spermatogenesis (Hussein et al, 2006) and protected the epithelial height of the seminiferous tubule in poisoned animals by pesticides (Sarabia et al). In addition to these findings, it was found that the exogenous melatonin administration protect testis towards the oxidative stressinduced tissue damage emerges after pinealectomy (Tasdemir et al, 2012).…”
Section: Results Ans Discussionmentioning
confidence: 98%
“…However, melatonin administration in late afternoon had decreased diameter of seminiferous tubule in non-PE hamster and mice (Ng & Ooi; Ooi & Ng). Nonetheless, if the antioxidant activity considered of the melatonin, we noted that melatonin administration increased the diameter of the seminiferous tubules in the diabetic rats (Guneli et al, 2008), healed the harmful effects of the radiation in the testis, restarted the spermatogenesis (Hussein et al, 2006) and protected the epithelial height of the seminiferous tubule in poisoned animals by pesticides (Sarabia et al). In addition to these findings, it was found that the exogenous melatonin administration protect testis towards the oxidative stressinduced tissue damage emerges after pinealectomy (Tasdemir et al, 2012).…”
Section: Results Ans Discussionmentioning
confidence: 98%
“…The Melatonin Attenuates ... parameters in the DM group rats [10][11][12][13][14] . The protective effects of MLT (used herein as an antioxidant) on the testis tissue are consistent with the previous results in DM models [11,12,44] .…”
Section: Discussionmentioning
confidence: 99%
“…The MLT is a freeradical scavenger and wide-spectrum antioxidant, and it stimulates the gene expression of antioxidant and prooxidant enzymes. MLT treatment after alloxan-induced b-cell destruction has been reported recently [10][11][12][13][14] . These studies suggest that MLT treatment in DM regulates the antioxidant enzymes and decreases the degenerative changes.…”
Section: Introductionmentioning
confidence: 99%
“…EXPERIMENTAL MODELS D Di ia ab be et te es s m me el ll li it tu us s ( (D DM M) ) m mo od de el l: : DM was induced by administration of intraperitoneal STZ (S0130-1G, Sigma, Aldrich) (dissolved in citrate buffer of pH 4.5) at a dose of 45 mg/kg to the rats. 17 On the 3rd day after STZ administration, nonfasting serum glucose levels were measured using a Medisense Optium glucometer (Roche Diagnostic, Germany). Rats with blood glucose levels higher than 250 mg/dl were considered as diabetic.…”
Section: Methodsmentioning
confidence: 99%